Soft, Implantable Bioelectronic Interfaces for Translational Research. Issue 17 (16th March 2020) - Schiavone, Giuseppe; Fallegger, Florian; Kang, Xiaoyang; Barra, Beatrice; Vachicouras, Nicolas; Roussinova, Evgenia; Furfaro, Ivan; Jiguet, Sébastien; Seáñez, Ismael; Borgognon, Simon; Rowald, Andreas; Li, Qin; et al.
Abstract: The convergence of materials science, electronics, and biology, namely bioelectronic interfaces, leads novel and precise communication with biological tissue, particularly with the nervous system. However, the translation of lab‐based innovation toward clinical use calls for further advances in materials, manufacturing and characterization paradigms, and design rules. Herein, a translational framework engineered to accelerate the deployment of microfabricated interfaces for translational research is proposed and applied to the soft neurotechnology called electronic dura mater, e‐dura. Anatomy, implant function, and surgical procedure guide the system design. A high‐yield, silicone‐on‐silicon wafer process is developed to ensure reproducible characteristics of the electrodes. A biomimetic multimodal platform that replicates surgical insertion in an anatomy‐based model applies physiological movement, emulates therapeutic use of the electrodes, and enables advanced validation and rapid optimization in vitro of the implants. Functionality of scaled e‐dura is confirmed in nonhuman primates, where epidural neuromodulation of the spinal cord activates selective groups of muscles in the upper limbs with unmet precision. Performance stability is controlled over 6 weeks in vivo. The synergistic steps of design, fabrication, and biomimetic in vitro validation and in vivo evaluation in translational animal models are of general applicability and answer needs in multiple bioelectronic designs and medical technologies. Abstract : Four synergistic steps of design, fabrication, and biomimetic in vitro validation and in vivo evaluation in translational animal models are proposed to advance soft implantable bioelectronics toward use in translational research. A biomimetic multimodal platform combines anatomy, mechanical loading, and electrochemical function to accelerate in vitro optimization of soft microtechnology.